Computational And Experimental Study On Horizontal-Axis Wind Turbine Slotted Blade Design - Ling, Siok Mei (Universiti Sains Malaysia, 2018)
The exponentially growth of wind energy installations around the globe in the decade has shown of the importance role of renewable energy in our community. The optimisation of wind turbine technology is essential in term of increasing the feasibility of costs, impact and productivity as the growing global demand on wind energy production. The optimised topology design of wind turbine blade is expecting to overcome the problem of relatively low wind speed exhibits in Malaysia in order to meet the requirement of utility-scale wind power plant. The current works include the development of unconventional slotted blade of three-blade arrangement horizontal-axis wind turbine. The aerofoil shape is chosen according to National Advisory Committee for Aeronautics (NACA) standard of 5 digit series. In this case, the referencing aerofoil shape is NACA63-415. The slotted blade is also created based on the previous research on the slotted flap on the aerofoil. The designing methodology of this study is first using computer aided design modelling software to develop the model, followed by utilizing a computational fluid dynamics software to simulate a two-dimensional aerofoil. In the experiment, the blades are produced by using 3D rapid prototyping and tested in an open-circuit wind tunnel. The comparison lift and drag coefficient between improved design and standard blade are carried out experimentally and numerically. The numerical results show that the lift coefficient of blade been improved with achievable of maximum value, 0.2799 or 42.8% higher compared to standard blade. Simultaneously, the drag of slotted blade also increased to a maximum value of 0.04022 compared to standard blade of 0.01111. The overall aerodynamic performance of slotted blade is lower than standard blade due to lower lift to drag coefficient ratio. Additionally, for experimental results, the maximum lift coefficient of slotted blade 0.2763. For standard blade, the maximum lift coefficient is 0.2600 which slightly lower than slotted blade. Maximum drag coefficient of slotted blade is 0.4341 in contrast with standard blade coefficient that is 0.130.